2023
DOI: 10.1007/s11368-023-03666-w
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off in activated biochar capping of complex sediment contamination: reduced PAH transport at the cost of potential As mobilisation

Gabrielle Dublet-Adli,
Gerard Cornelissen,
Espen Eek
et al.

Abstract: Purpose The effect of thin-layer capping with activated biochar on sediment-to-water flux was investigated. For the first time, the diffusion of both polycyclic aromatic hydrocarbons (PAHs) and arsenic (As) were studied simultaneously. The fate of As was investigated, under successive dysoxic and oxic conditions, in order to assess and discuss potential trade-off effects when using biochar as an active sorbent for capping of multi-contaminated sediments. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This approach, while effective in reducing PAH flux, has been identified to potentially facilitate the mobilization of arsenic (As) under oxygen-rich conditions, thereby underscoring the critical need for strategies that carefully consider the dynamics of multiple pollutants. The study, which used sediment samples from Bureå bay in Sweden, demonstrated that activated biochar effectively decreased PAH diffusion but inadvertently increased As mobility [187]. This finding highlights the importance of a balanced assessment in the application of biochar capping techniques, especially in sediments contaminated with various pollutants, to prevent the exacerbation of contaminant dispersion, particularly with arsenic.…”
Section: Transport Mechanisms Of Pahs In Water Bodiesmentioning
confidence: 92%
See 1 more Smart Citation
“…This approach, while effective in reducing PAH flux, has been identified to potentially facilitate the mobilization of arsenic (As) under oxygen-rich conditions, thereby underscoring the critical need for strategies that carefully consider the dynamics of multiple pollutants. The study, which used sediment samples from Bureå bay in Sweden, demonstrated that activated biochar effectively decreased PAH diffusion but inadvertently increased As mobility [187]. This finding highlights the importance of a balanced assessment in the application of biochar capping techniques, especially in sediments contaminated with various pollutants, to prevent the exacerbation of contaminant dispersion, particularly with arsenic.…”
Section: Transport Mechanisms Of Pahs In Water Bodiesmentioning
confidence: 92%
“…Analyses revealed over 75% of PAHs originated from coal combustion and vehicle emissions [186]. In a very recent research, the adoption of innovative methods, specifically thin-layer capping with activated biochar, was explored to address the challenge of mitigating the migration of PAHs from sediments to aquatic systems [187]. This approach, while effective in reducing PAH flux, has been identified to potentially facilitate the mobilization of arsenic (As) under oxygen-rich conditions, thereby underscoring the critical need for strategies that carefully consider the dynamics of multiple pollutants.…”
Section: Transport Mechanisms Of Pahs In Water Bodiesmentioning
confidence: 99%